SA96. Schizophrenia and Schizophrenia-Spectrum Disorders in the First-Degree Relatives of Children and Adults With Schizophrenia: The UCLA Family Study - Subotnik, Kenneth (Schizophr Bull, 2017)
Background: No prior study of morbid risk in relatives of schizophrenia probands has, to our knowledge, focused solely on those with a recent onset of illness. Given that studies starting with chronic schizophrenia probands may exclude some individuals who have a more benign illness course, the examination of morbid risks among first-degree relatives of recent-onset schizophrenia patients is of substantial interest. Methods: The relatives of recent onset adult and childhood-onset probands were interviewed by the same diagnosticians using identical methods. We employed a diagnostic hierarchy to ensure that no relative received more than 1 schizophrenia-spectrum diagnosis. Community comparison probands were excluded if they had a psychotic or bipolar affective disorder, but other psychiatric disorders were allowed so as to approximate an epidemiologically representative sample as opposed to a “super normal” group. The Kaplan-Meier method was used to compare morbid risks between relatives of patient versus community comparison probands. Results: As hypothesized, we find clear evidence for a significantly higher risk of schizophrenia among the first-degree relatives of recent-onset adult schizophrenia probands (N = 309 relatives of 117 probands) than among the first-degree relatives of control probands (N = 139 relatives of 48 control probands). We also find that the risk of schizophrenia-spectrum personality disorders was clearly significantly higher among relatives of schizophrenia probands than of community control probands. Avoidant personality disorder and schizoid personality disorder also show evidence of significant aggregation among relatives of schizophrenia probands compared to relatives of control probands. Further, the previously demonstrated risk for schizophrenia-spectrum disorders among parents of the childhood-onset probands was approximately twice as high as for the relatives of adult schizophrenia probands. Conclusion: Even when the proband sample consists of patients with a recent first episode of psychosis, rather than chronic schizophrenia probands, risks for schizophrenia and schizophrenia-spectrum disorders are higher than in community control families. We find support for inclusion of avoidant personality disorder in the extended schizophrenia spectrum. The findings from this project are also consistent with the hypothesis that schizophrenia with an onset in childhood has a stronger familial component than adult-onset schizophrenia.